2020
DOI: 10.1242/jeb.224618
|View full text |Cite
|
Sign up to set email alerts
|

Path integration error and adaptable search behaviors in a mantis shrimp

Abstract: Mantis shrimp of the species Neogonodactylus oerstedii occupy small burrows in shallow waters throughout the Caribbean. These animals use path integration, a vector-based navigation strategy, to return to their homes while foraging. Here, we report that path integration in N. oerstedii is prone to error accumulated during outward foraging paths and we describe the search behavior that N. oerstedii employs after it fails to locate its home following the route provided by its path integrator. This search behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…As described by Patel & Cronin [5,10], we observed that animals would make tortuous paths away from the burrow until they located the food placed in the arena. After animals located the food, they would usually execute a fairly direct home vector towards the burrow.…”
Section: Results and Discussion (A) Neogonodactylus Oerstedii Uses Landmarks During Navigationmentioning
confidence: 59%
See 3 more Smart Citations
“…As described by Patel & Cronin [5,10], we observed that animals would make tortuous paths away from the burrow until they located the food placed in the arena. After animals located the food, they would usually execute a fairly direct home vector towards the burrow.…”
Section: Results and Discussion (A) Neogonodactylus Oerstedii Uses Landmarks During Navigationmentioning
confidence: 59%
“…Taken together with our previous work on mantis shrimp navigation [5,10], this work offers an opportunity to study the neural basis of navigation, learning, memory and decision making in stomatopods. Mushroom bodies, centres for arthropod learning and memory, are thought to play a prominent role in landmark learning in insects [30][31][32][33].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Furthermore, mantis shrimp of the species Neogonodactylus oerstedii exhibit impressive navigational abilities when returning to their burrows from foraging excursions. These animals use landmarks, if available, in parallel with path integration to quickly pinpoint the location of their burrows ( Patel and Cronin, 2020a , b , c ). The benthic habitats N. oerstedii occupy are abundant with potential visually informative features including sponges, coral, rock and aquatic vegetation: structures of distinct shapes and colors.…”
Section: Introductionmentioning
confidence: 99%